PENINGKATAN KUALITAS PENYUSUNAN RPP MELALUI MONITORING DAN EVALUASI PELAKSANAAN PROGRAM SEKOLAH OLEH GURU DI SDN 18 SUNGAI LIMAU - Nurmalis, Nurmalis (STKIP Pesisir Selatan, 2017)
Based on the observations that researchers have done in SDN 18 Sungai Limau, it is found that teachers' ability in preparing RPP is still low. The purpose of this study is to describe and obtain information about the preparation of RPP by teachers. This study is a school action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 10 teachers of SDN 18 Sungai Limau. The data were collected using obeservation sheets. Data were analyzed using percentages. The results show that with Monitoring and Evaluation can improve the preparation of teacher RPP In SDN 18 Sungai Limau. This is evidenced by the evaluation and monitoring can Improve the quality of preparation of teacher RPP In SDN 18 Sungai Limau from cycle I to cycle II. The average ability of teachers in improving the making of RPP in cycle I is 51.39 with less category, In cycle II is 85.46 Good.